(3GdUhGQe GdegQbI aj GdQO Ydi GdUhGYb GdeMQbIs - (3GdeQYTj GdJSJQj (B((3GdThTJQj(B)(3, VjGA GdOjf, hQ Gddg Hf TQja GdpqOjf YHO Gddg Hf VjGA GdOjf fhQ Gddg Hf eMeO TGg, J (B1019 (3g`s ((3CQVi GdMei HGdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEf GdTjN GdLGgd GdLGeO GdMGed ddRLGL GdcGed aj fbU GdaWQI hShA GdeRGL CHh GdeOQ Hf MLQ GdKGfj GdPj fTC aj MLQ QNGe GdGfMQGa hHQGe GdGYhLGL hQGL HeTGQcI GSe GdMGaX GdYSbdGfj(B...s
(3BNQgG (B:s
... (3hJVjjY GdhbJ ajgG dGf HWdGf GdChd jSJdRe HWdGf GdKGfj hcPG GdcdGe aj NdGaI YKeGf hGddg JYGdi GdeSJYGf (B.s
(3efShNI Yf fSNI cKjQI GdZdW JGQjNgG (B: 21 (3ThGd (B1115 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\52s
(3GdPQjYI (B15- 68 ( 618)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs